Modification of agility running technique in reaction to a defender in rugby union - Wheeler, K. W.; Sayers, M. G. L. (Journal of Sports Science & Medicine, 2010)
Three-dimensional kinematic analysis examined agility running technique during pre-planned and reactive performance conditions specific to attacking ball carries in rugby union. The variation to running technique of 8 highly trained rugby union players was compared between agility conditions (pre-planned and reactive) and also agility performance speeds (fast, moderate and slow). Kinematic measures were used to determine the velocity of the centre of mass (COM) in the anteroposterior (running speed) and mediolateral (lateral movement speed) planes. The position of foot-strike and toe-off was also examined for the step prior to the agility side- step (pre-change of direction phase) and then the side-step (change of direction phase). This study demonstrated that less lateral movement speed towards the intended direction change occurred during reactive compared to pre-planned conditions at pre-change of direction (0.08 ± 0.28 m·s-1 and 0.42 ± 0.25 m·s-1, respectively) and change of direction foot-strikes (0.25 ± 0.42 m·s-1 and 0.69 ± 0.43 m·s-1, respectively). Less lateral movement speed during reactive conditions was associated with greater lateral foot displacement (44.52 ± 6.10% leg length) at the change of direction step compared to pre-planned conditions (41.35 ± 5.85%). Importantly, the anticipation abilities during reactive conditions provided a means to differentiate between speeds of agility performance, with faster performances displaying greater lateral movement speed at the change of direction foot- strike (0.52 ± 0.34 m·s-1) compared to moderate (0.20 ± 0.37 m·s-1) and slow (-0.08 ± 0.31 m·s-1). The changes to running technique during reactive conditions highlight the need to incorporate decision-making in rugby union agility programs.